Personaliti malu dan psikologi membuat keputusan di kalangan pelajar melayu - Khairul Anwar Mastor (Universiti Kebangsaan Malaysia, 2006)
The paper reports a study on self-consciousness from the Five Factor Model personality trait perspetctives and its relationship with the psychology of making decision in academic major at university level. Samples consist of 451 Malay students from different matriculation centers. Instrument used was the questionnaire on levels of confidence, satisfaction, persistence and difficulty in making decision of academic major. Personality profiles were measured by the NEO PI-R (Costa & McCrae, 1992). Results indicated that there were significant differences on scores of self-consciousness between male and female students. Female students scored higher on self-consciousness than male students. Female students also find they have difficulty in making decision and lower choice satisfaction. Correlation coefficients show that self-consciousness have relationships with other personality traits and levels of choice satisfaction and difficulty. Implications on the ability to make decision among Malay students were discussed